HOLY QURAN RECITATION OF SURAH AL-MULK AND AL-HASYR ON DECREASING ANXIETY IN MEDICAL STUDENTS - Kaima Ishmata Rianti; Indri Seta Septadina; Bintang Arroyantri Prananjaya (International Islamic Medicine Forum, 2021)
Anxiety is a feeling of discomfort, worry about something unclear and accompanied by autonomic symptoms. Holy Quran recitation therapy is one of the anxiety complementary therapies. This study is aimed to analyze the effect of the murottal Quran Surah Al-Mulk and Al-Hasyr on the anxiety of medical students of Universitas Sriwijaya. This research is a quasi-experimental study with a cross-sectional approach and one group pre-post test design that was conducted from July to December 2020 at home via Zoom meeting application. Samples were collected based on simple random sampling rocedure. The data was collected in this study is primary data based on Beck Anxiety Inventory (BAI) questionnaire before and after receiving the Quran recitation surah Al-Mulk and Al-Hasyr for 7 consecutive days. The data was analyzed with Shapiro-Wilk normality test and Paired t-test or Wilcoxon test using SPSS device. The Wilcoxon test results showed significant results of murottal Al-Qur'an surah Al-Mulk and Al-Hasyr on anxiety (p = 0.000). There is an effect of holy Quran recitation of surah Al-Mulk and Al-Hasyr on anxiety among medical students of Universitas Sriwijaya.